Performance improvement of flapping foils in von Karman wake. (1st January 2022) - Li, Jian; Wang, Xinjing; An, Xiaoyi; Zhang, Baoshou; Lyu, Da; Wang, Peng
Abstract: Flapping foils have been widely studied with the aim of achieving improved self-propelling efficiency and developing a new type of energy harvester. This study investigated the interaction of a flapping foil and the oncoming von Karman wake generated by a D-section cylinder. Distance between foil and cylinder, flapping frequency, and foil thickness are studied for the effects on the hydrodynamic performance of the flapping foil. The highest propulsive efficiency with the value of 50.33% was obtained when the non-dimensional frequency was 0.3, and the flapping foil operated as an energy harvester when the oscillating frequency was close to that of the wake. Furthermore, the original drag-generating flapping motion provided thrust when the foil thickness reached 20%. The definition of energy transformation ratio ( R ET ) was supplemented. Equations for the propulsive efficiency and energy harvesting efficiency were unified into one formula using R ET . When the value was in the ranges of (−1, 1) and (-Infinity, −1), the flapping foil operated as a propeller and an energy harvester, respectively. To summarize, the oncoming von Karman wake excited the flapping motion, indicating that a macro-underwater vehicle would perform better following a blunt body and an energy harvester with a flapping foil structure would work more efficiently behind underwater structures, such as the pillars of offshore platforms. Highlights: Energy transformation rate ( R ET ) is defined, where propelling and energy harvesting efficiency are unified with one formula. The results indicate that the macro underwater vehicle performs better following a blunt body. Energy harvesting efficiency reaches 39.81% working behind underwater structures such as pillars of the offshore platforms. The flapping foil works as an energy harvester when the oscillating frequency is close to that of the wake.